W stronę badań nad tytułami albumów fonograficznych: tzw. albumy eponimiczne - Radosław Marcinkiewicz (Stylistyka)
Proper names selected for musical albums are constantly changing. Certain consensus in the naming nomenclature was reached in the 1960s so that now most album names contain an ideonym and a name of a musical group. However, some names are eponymous in the sense that a name of a musical group serves as a title of an album. This is more typical of debut albums as it aids the new musical groups in reaching a wider audience. The article analyses the issue from a more complex perspective, as the selection of such a title is not always driven by the need to reduce the number of proper names. Other issues are also raised in the paper, including the difficulties related to the selection of a proper name for a musical album as well as the influence of musical genre on the naming tendencies.